THE INFLUENCE OF SELF-PRESENTATION THROUGH ROBLOX AVATARS ON ADOLESCENTS’ SELF-EFFICACY - Iqomul Ma'wah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Advances in digital technology have transformed the way adolescents express themselves and construct identities through virtual interactions, particularly on the Roblox platform. This study aims to analyze the influence of self-presentation through Roblox avatars on adolescents’ self-efficacy. The research employed an associative quantitative approach involving 101 adolescents aged 15–18 years in Surabaya selected through purposive sampling. The research instruments consisted of the Online Self-Presentation Scale and the General Self-Efficacy Scale. Simple linear regression analysis revealed a significant positive effect of avatar self-presentation on adolescents’ self-efficacy (F=202.022, p<0.001). The coefficient of determination (R²) value of 0.671 indicates that self-presentation contributes 67.1% to the variance in adolescents’ self-efficacy. These findings indicate that self-representation through virtual avatars plays a role in strengthening adolescents’ confidence in their abilities within digital social contexts. This study contributes to the development of digital social psychology studies, particularly regarding the relationship between virtual identity and adolescents’ psychological development in the era of interactive media. ABSTRAK Kemajuan teknologi digital telah mengubah cara remaja mengekspresikan diri dan membangun identitas melalui interaksi virtual, khususnya pada platform Roblox. Penelitian ini bertujuan untuk menganalisis pengaruh self-presentation melalui avatar Roblox terhadap self-efficacy remaja. Penelitian menggunakan pendekatan kuantitatif asosiatif dengan melibatkan 101 remaja berusia 15–18 tahun di Surabaya yang dipilih menggunakan teknik purposive sampling. Instrumen penelitian terdiri atas Online Self-Presentation Scale dan General Self-Efficacy Scale. Analisis regresi linear sederhana menunjukkan adanya pengaruh positif yang signifikan antara self-presentation avatar terhadap self-efficacy remaja (F=202.022, p<0.001). Nilai koefisien determinasi (R²) sebesar 0,671 menunjukkan bahwa self-presentation memberikan kontribusi sebesar 67,1% terhadap variasi self-efficacy remaja. Temuan ini mengindikasikan bahwa representasi diri melalui avatar virtual berperan dalam memperkuat keyakinan remaja terhadap kemampuan dirinya pada konteks sosial digital. Penelitian ini berkontribusi dalam memperkaya kajian psikologi sosial digital, khususnya terkait hubungan identitas virtual dan perkembangan psikologis remaja di era media interaktif.